1992
DOI: 10.1152/jn.1992.68.5.1910
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous nitric oxide required for an integrative respiratory function in the cat brain

Abstract: 1. The involvement of nitric oxide (NO) in the respiratory function of the pons was examined by microinjecting NO synthase-related drugs into discrete regions of the pontine respiratory group (PRG) in decerebrate and decerebellate cats. 2. Microinjection of N omega-nitro-L-arginine (L-NNA, inhibitor of NO synthase), but not D-NNA (the inactive enantiomer), significantly prolonged the duration of inspiration in all 10 cats when lung inflation was withheld. 3. The prolongation of inspiration produced by L-NNA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 0 publications
1
16
1
Order By: Relevance
“…There is also experimental evidence that NO modulates e.g. drinking behaviour (Calapai et al, 1992), nociception (Moore et al, 1991), integrative respiratory function (Ling et al, 1992), and wakefulness (Kapas et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…There is also experimental evidence that NO modulates e.g. drinking behaviour (Calapai et al, 1992), nociception (Moore et al, 1991), integrative respiratory function (Ling et al, 1992), and wakefulness (Kapas et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with this model, postsynaptic activation of NMDA receptors and opening of calcium channels associated with these receptors produce an increased level of intracellular Ca 2+ that, via calmodulin, activates NO synthase. Microinjections of an inhibitor of NO synthase into the region of pontine respiratory neuronal grouping of adult decerebrated and decerebellated cats prolong inspiration (in a test without swelling the lungs) [10]. This shows that the effect of activation of the NMDA receptors in the framework of a pontine pneumotaxic function is mediated by NO.…”
Section: Discussionmentioning
confidence: 86%
“…At the same time, NO is known to be involved in the control of neuronal activity in the ventrolateral region of the medulla (VLM) [6,7 ], where the bulbar respiratory generator is localized [8,9]. In cats, endogenous NO is shown to be involved in functioning 334 0090-2977/97/29060334518.00 01998 Plenum Publishing Corporation of the pontine pneumotaxic center [10]. The NO role in pathogenesis of hypoxia and ischemia of the brain attracts special attention.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that NO enhances the excitability and spontaneous discharge rates of neurons in the NTS (27) and may act as a retrograde messenger in an L-glutamate-releasing positive feedback system, also in the NTS, involved in the increase of ventilation during hypoxia (24). NO has an excitatory effect on the discharge rates of neurons in the pontine respiratory group, whereas L-NNA produces a disruption of the pneumotaxic mechanism (28).…”
Section: Discussionmentioning
confidence: 99%